Prophets without honor : a requiem for moral patriotism - Strabala, William (Algora Pub., 2002)
"Radical priests" laid it on the line, challenging government, corporations and the Church. Some were jailed; some were killed. Personal accounts tell why they had to do it -- and why governments and the Church fought so hard to stop them. The book tells the story of a group of American men who happen to be priests and who happen to have served decades in American prisons and the stalwart women who helped them form an international movement called Plowshares. In so doing, the book tells the morally patriotic story of America, a story told before only from behind an open hand across the face, like a football coach talking to his spotters in full view of a national television audience, afraid someone might see. Darrell Rupiper, Larry Rosebaugh and Carl Kabat are Oblate missionary priests. Frank Cordaro is a diocesan priest from Des Moines. Roy Bourgeois is a Maryknoll priest. Charlie Liteky is an ex-Trinitarian priest. Rupiper was in the national spotlight during the Iran hostage crisis. He traveled to Iran as part of team of clerics hoping to gain the release of the hostages. Rosebaugh now lives with the poor in El Salvador. He was a member of the Milwaukee 14, a group that burned draft records in accord with the example set by the Berrigan brothers at Catonsville, Maryland in 1968. Kabat has served over 16 years in United States federal and state prisons since 1980 as a result of his anti-military actions. Cordaro has served half a dozen federal prison terms for his anti-nuclear activities. He has also given sanctuary to a manure spreader in support of Iowa farmers. During the Carter presidency Cordaro found himself on the front page of the Washington Post after he stood in front of Carter during a press conference to tell the world the truth about the S.A.L.T. treaty. Bourgeois, from the deep South and a former military officer who served in Vietnam, recently made his own front-page news [N.Y. Times, Washington Post and others] as leader of the massive protests at Fort Benning, Georgia calling for the closing of the School of the Americas. Bourgeois and Rosebaugh also served prison terms in the 1980s when they sneaked into Fort Benning, climbed a tree and played a tape outside the Salvadoran soldiers' barracks of the last sermon given by slain archbishop Oscar Romero. Liteky is a former chaplain who served in Vietnam. He received the Congressional Medal of Honor, and later surrendered it, challenging General Abrams and President Nixon in the process. With the exception of Cordaro, all of these men began their clerical careers as missionaries, in Brazil, the Philippines, Bolivia and Vietnam, and discovered America in the process. They discovered that the trail of the poor leads through such countries directly back to America. It leads directly to Rupiper's home in Carroll, Iowa; to Rosebaugh and Kabat's roots in rural Illinois; to Cordaro's Des Moines Italian household and to the nation's capital, where Liteky was born. They also discovered that the America they grew up in never existed. They read history and learned about America's militarism, its attempts at global hegemony, and they felt they must resist. They wanted with all their hearts for their childhood America to be made real -- a just and loving America -- even if that meant they must spend years behind prison walls